Ultrahigh-strength steel as well as preparation method and application thereof

By using smelting, casting, forging, rolling and heat treatment methods in the preparation process of ultra-high strength steel, the problems of difficult and high cost are solved, and the preparation of smelting, casting, forging, rolling and heat treatment are achieved under low cost and simple process conditions are achieved. Ultra-high strength and good plasticity steel products.

CN119433383APending Publication Date: 2025-02-14SOUTHWEST JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411119256.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the preparation process of ultra-high strength steel, there are problems of difficult processing and high cost. How to obtain ultra-high strength steel products with strong applicability and good plasticity under the regulation of low cost and simple post-treatment process? Technical problems that need to be solved urgently in the field of ultra-high strength steel.

Method used

High-quality medium-carbon low-alloy steel ingots are obtained by smelting and casting, followed by forging and rolling, and finally, ultra-high strength steel with good plasticity is obtained by heat treatment. This method does not require a large amount of alloy elements to regulate, and does not require deformation heat treatment, which is simple to operate and low cost.

Benefits of technology

It has achieved the preparation of steel products with ultra-high strength and good plasticity under low cost and simple process conditions. It is suitable for the preparation of a variety of ultra-high strength steels with different properties. It is simple to operate, low cost and has broad prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119433383A_ABST
    Figure CN119433383A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of ultrahigh-strength steel, and provides ultrahigh-strength steel as well as a preparation method and application thereof. According to the method, firstly, high-quality medium-carbon low-alloy steel ingots are obtained through smelting and casting, then the steel profiles are obtained through forging and rolling, the ultrahigh-strength steel with different metallographic structures is obtained through heat treatment, and preparation of the ultrahigh-strength steel with multiple different purposes is achieved. According to the preparation method provided by the invention, a large amount of nickel, cobalt, molybdenum and other elements do not need to be added to improve the alloy strength, deformation heat treatment is not needed, preparation of the ultra-high-strength steel with various different properties can be realized only by performing proper heat treatment after the steel profile is obtained, the operation is simple, the cost is low, and the method has a wide prospect. Furthermore, the adopted alloy raw material is scrap steel, and only trace alloy elements need to be adopted for adjustment during smelting, so that the preparation cost of the ultrahigh-strength steel is reduced, and the reutilization of the scrap steel is also realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ultra-high strength steel, and in particular to ultra-high strength steel and a preparation method and application thereof. Background Art

[0002] Ultra-high strength steel (UHSS) mainly refers to high-strength structural steel with room temperature yield strength greater than 1180MPa and tensile strength greater than 1380MPa. At present, ultra-high strength steel is mainly used to manufacture key structural parts that withstand high stress, especially ultra-high strength steel with a tensile strength of more than 2000MPa, which can be used to prepare important parts such as aircraft landing gear, ultra-high-speed bearings, bridge cables, ultra-high-strength bolts, molds, etc., and is widely used in aerospace, high-end equipment, major engineering and other fields. In short, ultra-high strength steel has broad development prospects and has always been one of the key development directions in the field of steel research at home and abroad.

[0003] Strength and plasticity are important mechanical performance indicators of steel materials, and they are also a pair of inherent contradictions. In the field of transportation, the higher the strength of the material, the less it can be used in actual application, achieving the goal of weight reduction and energy saving; the better the plasticity, the higher the safety factor of the vehicle. How to maintain good plasticity under ultra-high strength has always been a core issue to be solved in the field of ultra-high strength steel.

[0004] In the preparation process of ultra-high strength steel, the strength of steel is improved mainly through the following two ways: one way is to combine alloying with heat treatment, and improve the microstructure and performance of steel by adding a large amount of alloy elements and regulating the heat treatment process. Typical examples are maraging steel and precipitation hardening steel. Maraging steel usually requires the addition of more alloying elements such as nickel, cobalt, and molybdenum. For example, a Chinese patent application with publication number CN103484787A provides a maraging steel with the chemical composition of: 0.10wt.%≤C≤0.30wt.%, 6.0wt.%≤Ni≤9.4wt.%, 11.0wt.%≤Co≤20.0wt.%, 1.0wt.%≤Mo≤6.0wt.%, 2.0wt.%≤Cr≤6.0wt.%, 0.5wt.%≤Al≤1.3wt.%, Ti≤0.1wt.%, and the remainder is Fe and unavoidable impurities, among which the contents of elements such as nickel, cobalt, and molybdenum are all relatively high. Precipitation hardening steel is a type of stainless steel with high strength, high toughness and high corrosion resistance obtained by adding hardening elements to various types of stainless steel alone or in combination, wherein a large amount of elements such as nickel and chromium are usually added. For example, a precipitation hardening steel is provided in the Chinese patent application with publication number CN109642299A, and its chemical composition is: C: 0.05-0.30wt.%, Ni: 3-9wt.%, Mo: 0.5-1.5wt.%, Al: 1-3wt.%, Cr: 2-14wt.%, V: 0.25-1.5wt.%, Co: 0-0.03wt.%, Mn: 0-0.5wt.%, Si: 0-0.3wt.%, and the rest is Fe and impurity elements. Although the strength of steel is improved by adding alloying elements, the operation is simple and batch manufacturing and production are easy to realize, but the difficulty of smelting, processing difficulty and cost of steel will increase significantly, and it is difficult to promote and apply on a large scale.

[0005] Another way to improve steel strength is thermomechanical treatment, which combines pressure processing (such as forging and rolling) with heat treatment to achieve strengthening by controlling the phase change process and phase change products. This method is only suitable for one-time formed products, and is not suitable for heat treatment and surface chemical heat treatment of products after processing and forming; and the thermomechanical treatment process requires the combination of pressure processing and heat treatment operations, which increases the complexity of the production process and limits its wide application.

[0006] In summary, the current preparation process of ultra-high-strength steel has problems such as high processing difficulty and high cost. How to obtain ultra-high-strength steel products with strong applicability and good plasticity at a lower cost and with simple post-processing process control is a technical problem that needs to be solved urgently in the field of ultra-high-strength steel. Summary of the invention

[0007] In view of this, the present invention provides ultra-high strength steel and its preparation method and application. The present invention obtains high-quality medium-carbon low-alloy steel ingots (medium-carbon low-alloy steel ingots refer to steel with a carbon content between 0.25wt.% and 0.60wt.%, and a total amount of alloy elements less than 5wt.%) through smelting and casting, and then obtains steel profiles through forging and rolling, and then obtains ultra-high strength steel with good plasticity through heat treatment; the preparation process of the present invention does not require a large amount of alloy element regulation, and does not require deformation heat treatment, the operation is simple, the cost is low, and it has broad prospects.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] A method for preparing ultra-high strength steel comprises the following steps:

[0010] The alloy raw material is melted and then cast to obtain a steel ingot; the chemical composition of the steel ingot includes: C: 0.53-0.57wt.%, Si: 1.5-1.8wt.%, Mn: 0.80-1.0wt.%, Mo: 0.15-0.20wt.%, V: 0.10-0.15wt.%, Cr: 0.30-0.40wt.%, Ni: 0.10-0.15wt.%, Cu: 0.05-0.08wt.%, Nb: 0.01-0.02wt.%, Al≤0.05wt.%, P≤0.010wt.%, S≤0.010wt.%, O≤12ppm, N≤20ppm, and the balance is Fe;

[0011] Forging and rolling the steel ingot in sequence to obtain a steel profile;

[0012] The steel profile is heat treated to obtain the ultra-high strength steel; the metallographic structure of the ultra-high strength steel includes nano-sheet twinned martensite; or the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite; or the metallographic structure of the ultra-high strength steel includes tempered troostite.

[0013] Preferably, the alloy raw materials include scrap steel with a grade of 60Si2MnA, scrap steel with a grade of 50CrVA and scrap steel with a grade of 40CrNiMo.

[0014] Preferably, the scrap steel with a grade of 60Si2MnA is scrap railway spring bars; the scrap steel with a grade of 50CrVA is scrap automobile leaf springs; and the scrap steel with a grade of 40CrNiMo is scrap shafts.

[0015] Preferably, the smelting includes: coarsely refining the alloy raw material and then adjusting and refining the alloy elements in sequence.

[0016] Preferably, the mass ratio of the scrap steel with the grade of 60Si2MnA, the scrap steel with the grade of 50CrVA and the scrap steel with the grade of 40CrNiMo is (4-6):(2-4):(1-2).

[0017] Preferably, before the rough refining, the alloy raw material is subjected to surface cleaning and preheating treatment in sequence.

[0018] Preferably, the surface cleaning is shot blasting cleaning.

[0019] Preferably, the preheating treatment is carried out at a temperature of 500-600° C. for 30-50 min; and the preheating treatment is carried out under nitrogen protection.

[0020] Preferably, the raw materials used for adjusting the alloy elements include one or more of ferrosilicon, ferromanganese, aluminum-containing deoxidizer, ferromolybdenum, ferrovanadium, waste copper wire with insulation removed, and ferroniobium.

[0021] Preferably, the roughing is electric arc furnace roughing; and the refining is ladle refining.

[0022] Preferably, the steel is tapped from an electric arc furnace after the alloy elements are adjusted. The tapping temperature of the electric arc furnace is 1700-1750° C., and bottom blowing of argon is performed 5-10 minutes before tapping.

[0023] Preferably, the refining temperature is 1680-1720° C., the refining time is 40-60 min, and argon is blown and stirred throughout the refining process.

[0024] Preferably, the casting is vacuum casting; the temperature of the molten steel during the vacuum casting is 1630-1670° C.; the vacuum degree of the vacuum casting is 30-50 Pa.

[0025] Preferably, before the vacuum casting, the molten steel is also vacuum degassed.

[0026] Preferably, the initial forging temperature of the forging is 1050-1100°C, and the final forging temperature is 950-1000°C.

[0027] Preferably, the rolling is hot rolling; the initial rolling temperature of the hot rolling is 900-950°C, and the final rolling temperature is 850-875°C; the number of hot rolling passes is 8-10 passes; and the deformation rate of the hot rolling passes is 5%-15%.

[0028] Preferably, the steel profile is a steel wire; the diameter of the steel wire is 15 to 30 mm.

[0029] Preferably, when the metallographic structure of the ultra-high strength steel includes nanosheet twinned martensite, the heat treatment includes: subjecting the steel profile to austenitizing heat treatment and salt bath isothermal quenching in sequence; the temperature of the austenitizing heat treatment is 870-890°C, and the holding time is 20-30 min; the austenitizing heat treatment is carried out under nitrogen protection; the temperature of the salt bath isothermal quenching is 150-180°C, the isothermal holding time is 20-40 min, and water cooling to room temperature after isothermal holding.

[0030] Preferably, when the core metallographic structure of the ultra-high strength steel includes medium-carbon martensite and lower bainite, and the surface metallographic structure includes high-carbon martensite, granular carbide and lower bainite, the heat treatment includes: subjecting the steel profile to carburizing heat treatment and salt bath isothermal quenching in sequence; the carburizing heat treatment temperature is 870-890°C, the holding time is 1-2h, and the carbon potential is 1-1.1; the salt bath isothermal quenching temperature is 200-250°C, the isothermal holding time is 20-30min, and water cooling to room temperature after isothermal holding.

[0031] Preferably, when the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite, the surface C element content of the ultra-high strength steel is 0.90-1.0wt.%.

[0032] Preferably, when the metallographic structure of the ultra-high strength steel includes tempered troostite, the heat treatment includes: quenching and tempering the steel profile in sequence; the heating temperature of the quenching is 870-890°C, the holding time is 20-30 minutes, and the heating process of the quenching is carried out under argon protection; the cooling method of the quenching is water cooling and air cooling in sequence; the temperature of the water for water cooling is 40°C, and the water cooling time is 5-10 seconds; the air cooling is air cooling to room temperature; the tempering temperature is 480-520°C, and the holding time is 40-60 minutes; the tempering is carried out under nitrogen protection; the cooling method of the tempering is water cooling.

[0033] The present invention also provides an ultra-high strength steel prepared by the preparation method described in the above scheme; the metallographic structure of the ultra-high strength steel includes nanosheet twinned martensite; or the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite; or the metallographic structure of the ultra-high strength steel includes tempered troostite.

[0034] Preferably, when the metallographic structure of the ultra-high strength steel includes nanosheet twinned martensite, the volume fraction of the twinned martensite in the metallographic structure is 98-100%; the tensile strength of the ultra-high strength steel is above 2.7 GPa, the yield strength is above 1.8 GPa, and the elongation is above 9%.

[0035] Preferably, when the core metallographic structure of the ultra-high strength steel includes medium-carbon martensite and lower bainite, and the surface metallographic structure includes high-carbon martensite granular carbide and lower bainite, the volume fraction of medium-carbon martensite in the metallographic structure of the core is 85-90%, and the volume fraction of lower bainite is 10-15%; the volume fraction of high-carbon martensite in the surface metallographic structure is 80-90%, the volume fraction of granular carbide is 5-10%, and the volume fraction of lower bainite is 5-10%; the surface hardness of the ultra-high strength steel is 62-64HRC, and the surface hardness is 850-950HV.

[0036] Preferably, when the metallographic structure of the ultra-high strength steel includes tempered troostite, the volume fraction of tempered troostite in the metallographic structure is 80-90%; the yield strength of the ultra-high strength steel is above 1300 MPa, the tensile strength is above 1500 MPa, and the elongation is above 10%.

[0037] The present invention also provides the use of the ultra-high strength steel described in the above scheme in aircraft landing gear, bearings, bridge cables, bolts and molds.

[0038] The present invention also provides the use of the ultra-high strength steel described in the above scheme in wear-resistant products.

[0039] The present invention also provides the use of the ultra-high strength steel described in the above solution in elastic components.

[0040] The invention provides a method for preparing ultra-high strength steel, comprising the following steps: melting an alloy raw material and then casting to obtain a steel ingot; the chemical composition of the steel ingot comprises: C: 0.53-0.57wt.%, Si: 1.5-1.8wt.%, Mn: 0.80-1.0wt.%, Mo: 0.15-0.20wt.%, V: 0.10-0.15wt.%, Cr: 0.30-0.40wt.%, Ni: 0.10-0.15wt.%, Cu: 0.05-0.08wt.%, Nb: 0.01-0.02wt.%, Al≤0.05wt.%, P≤0.010wt.%, S≤0.010wt.%, O≤12ppm, N≤20ppm, and the balance is Fe; the steel ingot is forged and rolled in sequence to obtain a steel profile; the steel profile is heat treated to obtain the ultra-high strength steel; the metallographic structure of the ultra-high strength steel includes nanosheet twin martensite; or the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite; or the metallographic structure of the ultra-high strength steel includes tempered troostite. The present invention first obtains high-quality medium-carbon low-alloy steel ingots by smelting and casting, then obtains steel profiles by forging and rolling, and then obtains ultra-high-strength steels with different metallographic structures by heat treatment. The ultra-high-strength steels with different metallographic structures have different properties and uses; wherein, the ultra-high-strength steel whose metallographic structure includes nano-sheet twin martensite has ultra-high strength (tensile strength is above 2.7GPa) and good plasticity (elongation is above 9%), and can be applied to the preparation of key structural parts subjected to high stress such as bridge cables; the ultra-high-strength steel whose core metallographic structure includes medium-carbon martensite and lower bainite, and whose surface metallographic structure includes high-carbon martensite, granular carbide and lower bainite has high surface hardness, and can be used for the preparation of wear-resistant products such as bearing rollers and tools and dies; the ultra-high-strength steel whose metallographic structure includes tempered troostite has high yield strength (above 1300MPa), tensile strength (above 1500MPa) and elongation (above 10%), and can be used for the preparation of elastic products such as spring bars, springs, and elastic gaskets. In summary, the preparation method provided by the present invention does not need to use a large amount of alloy elements such as nickel, cobalt, molybdenum, etc. to improve the strength of steel, and does not need to perform deformation heat treatment. It only needs to perform appropriate heat treatment after obtaining the steel profile. It is suitable for the preparation of ultra-high strength steels with various properties, is simple to operate, low in cost, and has broad prospects.

[0041] Furthermore, the alloy raw material used in the present invention is scrap steel, and only a trace amount of alloying elements need to be used for adjustment during smelting, which not only further reduces the preparation cost of ultra-high strength steel, but also realizes the reuse of scrap steel, turning waste into treasure.

[0042] Furthermore, the present invention also defines the corresponding heat treatment system when the ultra-high strength steel has different metallographic structures. The heat treatment system of the present invention can further ensure the excellent performance of the ultra-high strength steel. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Schematic diagram of the process of preparing steel profiles in an embodiment of the present invention;

[0044] Figure 2 The metallographic structure morphology of the steel wire obtained in Example 1;

[0045] Figure 3 The metallographic structure morphology of the ultra-high strength steel obtained after heat treatment in Example 2;

[0046] Figure 4 This is a SEM image of the microstructure of the ultra-high strength steel obtained after heat treatment in Example 2;

[0047] Figure 5 This is the alloy element distribution diagram of the ultra-high strength steel obtained after heat treatment in Example 2;

[0048] Figure 6 TEM image of the microstructure of the ultra-high strength steel obtained after heat treatment in Example 2, where a and b are bright field phases, c is a dark field phase, and d is a diffraction spot;

[0049] Figure 7 TEM image of the precipitated phase of the ultra-high strength steel obtained after heat treatment in Example 2, wherein a is a bright field image, b is a dark field phase, c is a high-resolution image at the interface with the matrix, d is a diffraction spot, and e, f, g, and h are the distribution of alloy elements in the precipitated phase;

[0050] Figure 8 The metallographic structure morphology of the steel sample obtained after heat treatment in Comparative Example 1;

[0051] Fig. 9 This is a SEM image of the microscopic morphology of the steel sample obtained after heat treatment in Comparative Example 1;

[0052] Fig.10 The stress-strain curves of the wire rod without heat treatment, the ultra-high strength steel obtained in Example 2, and the steel sample obtained in Comparative Example 1;

[0053] Fig.11 The surface metallographic structure morphology (left) and hardness distribution curve (right) of the ultra-high strength steel obtained after heat treatment in Example 3;

[0054] Fig.12 The metallographic structure morphology (left) and stress-strain curve (right) of the ultra-high strength steel obtained after heat treatment in Example 4. DETAILED DESCRIPTION

[0055] The present invention provides a method for preparing ultra-high strength steel, comprising the following steps:

[0056] The alloy raw material is melted and then cast to obtain a steel ingot; the chemical composition of the steel ingot includes: C: 0.53-0.57wt.%, Si: 1.5-1.8wt.%, Mn: 0.80-1.0wt.%, Mo: 0.15-0.20wt.%, V: 0.10-0.15wt.%, Cr: 0.30-0.40wt.%, Ni: 0.10-0.15wt.%, Cu: 0.05-0.08wt.%, Nb: 0.01-0.02wt.%, Al≤0.05wt.%, P≤0.010wt.%, S≤0.010wt.%, O≤12ppm, N≤20ppm, and the balance is Fe;

[0057] Forging and rolling the steel ingot in sequence to obtain a steel profile;

[0058] The steel profile is heat treated to obtain the ultra-high strength steel; the metallographic structure of the ultra-high strength steel includes nano-sheet twinned martensite; or the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite; or the metallographic structure of the ultra-high strength steel includes tempered troostite.

[0059] The present invention melts the alloy raw material and then casts it to obtain a steel ingot. In the present invention, the alloy raw material preferably includes scrap steel with a grade of 60Si2MnA, scrap steel with a grade of 50CrVA and scrap steel with a grade of 40CrNiMo; the scrap steel with a grade of 60Si2MnA is preferably scrap railway spring bars; the scrap steel with a grade of 50CrVA is preferably scrap automobile leaf springs; the scrap steel with a grade of 40CrNiMo is preferably scrap shafts; the mass ratio of the scrap steel with a grade of 60Si2MnA, the scrap steel with a grade of 50CrVA and the scrap steel with a grade of 40CrNiMo is preferably (4-6):(2-4):(1-2), and more preferably (4.5-5.5):(2.5-3.5):(1-1.5).

[0060] In the present invention, the smelting preferably includes: coarse refining the alloy raw material and then adjusting and refining the alloy elements in sequence; and argon gas stirring is conducted during the coarse refining, alloy element adjustment and refining processes.

[0061] In the present invention, before the rough refining, it is preferred that the alloy raw material is subjected to surface cleaning and preheating treatment in sequence; the surface cleaning is preferably shot blasting cleaning, and the anti-corrosion treatment layer, rust oxidation and oil stains and other impurities on the surface of the alloy raw material are removed by shot blasting cleaning; the temperature of the preheating treatment is preferably 500-600°C, more preferably 530-550°C; the time of the preheating treatment is preferably 30-50min, more preferably 35-45min; the preheating treatment is preferably carried out under nitrogen protection.

[0062] In the present invention, the rough refining is preferably electric arc furnace rough refining; the present invention has no special requirements on the specific conditions of the rough refining, as long as the alloy raw materials can be melted.

[0063] In the present invention, the raw materials used for adjusting the alloy elements preferably include one or more of ferrosilicon, ferromanganese, aluminum-containing deoxidizer, ferromolybdenum, ferrovanadium, scrap copper wire with insulation removed, and ferroniobium; the present invention has no special requirements for the aluminum-containing deoxidizer, and those familiar to those skilled in the art can be used; the present invention has no special requirements for the specific method of adjusting the alloy elements, and those familiar to those skilled in the art can be used; in a specific embodiment of the present invention, the above raw materials are added in a timely manner after the alloy raw materials are melted to adjust the composition of the molten steel to the required range. After the alloy elements are adjusted, the electric arc furnace is tapped, and the tapping temperature of the electric arc furnace is preferably 1700-1750°C, more preferably 1720-1730°C; argon is preferably blown from the bottom 5-10 minutes before tapping; and large amount of stirring is preferably used during tapping to ensure that the alloy raw materials are fully melted.

[0064] In the present invention, the refining is preferably ladle refining; the refining temperature is preferably 1680-1720°C, more preferably 1700°C; the refining time is preferably 40-60min, more preferably 45-55min; argon gas is blown for stirring throughout the refining process; the refining process preferably ensures submerged arc operation; in a specific embodiment of the present invention, the steel tapping is specifically to discharge the molten steel into a clean turnover ladle to ensure red envelope steel tapping, and the baking temperature of the ladle is preferably 1100-1200°C.

[0065] In the present invention, the casting is preferably vacuum casting; the temperature of the molten steel during the vacuum casting is preferably 1630-1670°C, more preferably 1650°C; the vacuum degree of the vacuum casting is preferably 30-50Pa, more preferably 35-45Pa; before the vacuum casting, the molten steel is preferably vacuum degassed; in a specific embodiment of the present invention, the molten steel is preferably transferred to a tundish after refining, and then vacuum degassed and vacuum cast. The casting obtains a steel ingot, and in a specific embodiment of the present invention, the diameter of the steel ingot is preferably 300mm.

[0066] In the present invention, the chemical composition of the steel ingot includes C: 0.53-0.57wt.%, preferably 0.54-0.55wt.%; too low a C content will result in insufficient strength, and too high a C content will result in poor toughness and plasticity; the chemical composition of the steel ingot includes Si: 1.5-1.8wt.%, preferably 1.6-1.7wt.%; too low a Si content will result in insufficient yield strength, and too high a Si content will result in poor toughness and plasticity; the chemical composition of the steel ingot includes Mn: 0.80-1.0wt.%, preferably 0.9-1.0wt.%; too high a Mn content will result in The cost is high and more residual austenite is obtained by quenching. If the content of Mn is too low, the strength and hardenability will be insufficient. The chemical composition of the steel ingot includes Mo: 0.15-0.20wt.%, preferably 0.15-0.18wt.%; if the content of Mo is too high, the cost will increase significantly. If the content of Mo is too low, the thermal strength will be insufficient and temper brittleness will be easily generated. The chemical composition of the steel ingot includes V: 0.10-0.15wt.%, preferably 0.12-0.15wt.%; if the content of V is too low, the thermal strength will decrease, the grain will be coarsened, etc., and if the content of V is too high, the cost will increase and it will be easy to form Coarse carbides affect toughness and plasticity; the chemical composition of the steel ingot includes Cr: 0.30-0.40wt.%, preferably 0.30-0.35wt.%; too low Cr content will affect strength and hardenability, and too high Cr content will increase costs; the chemical composition of the steel ingot includes Ni: 0.10-0.15wt.%, preferably 0.12-0.15wt.%; too low Ni content will lead to insufficient toughness and plasticity, and too high Ni content will significantly increase costs; the chemical composition of the steel ingot includes Cu: 0.05-0.08wt.%, preferably 0.05-0. 06wt.%; if the Cu content is too low, it will affect the toughness and fluidity of molten steel, and if the Cu content is too high, it will cause hot brittleness; the chemical composition of the steel ingot includes Nb: 0.01-0.02wt.%, preferably 0.01-0.015wt.%; if the Nb content is too low, it will affect temper brittleness and overheating sensitivity, and if the Nb content is too high, it will lead to increased cost and precipitation of a large amount of niobium carbide; the chemical composition of the steel ingot also includes Al: ≤0.05wt.%, P: ≤0.010wt.%, S: ≤0.010wt.%, O: ≤12ppm, N: ≤20ppm and the balance of Fe.

[0067] After obtaining the steel ingot, the present invention sequentially forges and rolls the steel ingot to obtain a steel profile. In the present invention, the initial forging temperature of the forging is preferably 1050-1100°C, more preferably 1060-1080°C, and the final forging temperature is preferably 950-1000°C, more preferably 960-980°C; the forging obtains a steel billet; in a specific embodiment of the present invention, the steel billet is preferably a square steel billet, and the cross-sectional size of the square steel billet is preferably 160mm×160mm.

[0068] In the present invention, the steel profile is a medium carbon low alloy steel profile, and medium carbon low alloy steel refers to steel with a carbon content between 0.25wt.% and 0.60wt.%, and a total amount of alloy elements less than 5wt.%.

[0069] In the present invention, the rolling is preferably hot rolling; in a specific embodiment of the present invention, it is preferred to use the forging waste heat of the steel billet after forging for rolling; the initial rolling temperature of the hot rolling is preferably 900-950°C, more preferably 930-950°C; the final rolling temperature of the hot rolling is preferably 850-875°C, more preferably 860-875°C; the number of hot rolling passes is preferably 8-10 passes; the deformation rate of the hot rolling passes is preferably 5%-15%.

[0070] After hot rolling, the present invention preferably performs insulation treatment on the obtained steel profile, and then air-cools it to room temperature; the temperature of the insulation treatment is preferably 550-650°C, more preferably 600°C, and the time is preferably 8-15min, more preferably 10min; after air-cooling to room temperature, it is also preferably included to perform surface processing on the air-cooled steel profile; the surface processing is preferably to remove the surface oxide scale and decarburized layer. In a specific embodiment of the present invention, it is preferred to process the surface layer of the steel profile to reduce the diameter of the steel profile by 1mm.

[0071] In the present invention, the steel profile is preferably a steel wire; in a specific embodiment of the present invention, the diameter of the steel wire (diameter before surface processing) is preferably 15 to 30 mm; when no heat treatment is performed, the metallographic structure of the steel profile includes pearlite and a small amount of ferrite.

[0072] After obtaining the steel profile, the present invention performs heat treatment on the steel profile to obtain the ultra-high strength steel; the metallographic structure of the ultra-high strength steel includes nanosheet twinned martensite; or the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite; or the metallographic structure of the ultra-high strength steel includes tempered troostite.

[0073] In the present invention, when the metallographic structure of the ultra-high strength steel includes nanosheet twin martensite, the heat treatment preferably includes: subjecting the steel profile to austenitizing heat treatment and salt bath isothermal quenching (referred to as the first salt bath isothermal quenching) in sequence; the temperature of the austenitizing heat treatment is preferably 870-890°C, more preferably 875-885°C, further preferably 880°C, and the holding time is preferably 20-30min, more preferably 20-25min; the austenitizing heat treatment is preferably carried out under nitrogen protection; the temperature of the first salt bath isothermal quenching is preferably 150-180°C, more preferably 160-170°C, the isothermal holding time is preferably 20-40min, more preferably 25-35min, and after isothermal holding, it is preferably water-cooled to room temperature. The present invention first performs austenitization at a temperature of 870-890°C, and then performs isothermal quenching in the martensitic phase transformation temperature zone to obtain a nano-sheet twin martensite structure, which has ultra-high strength and good plasticity. In the present invention, after heat treatment by such a heat treatment system, the metallographic structure of the obtained ultra-high strength steel is basically all nano-sheet twin martensite. In a specific embodiment of the present invention, after heat treatment by such a heat treatment system, the obtained ultra-high strength steel also includes a nano alloy carbide precipitation phase.

[0074] In the present invention, when the metallographic structure of the core of the ultra-high strength steel includes medium-carbon martensite and lower bainite, and the surface metallographic structure includes high-carbon martensite, granular carbide and lower bainite, the heat treatment preferably includes: subjecting the steel profile to carburizing heat treatment and salt bath isothermal quenching (recorded as the second salt bath isothermal quenching) in sequence, and then water cooling to room temperature; the temperature of the carburizing heat treatment is preferably 870-890°C, more preferably 880°C, the holding time is preferably 1-2h, more preferably 1-1.5h, and the carbon potential is preferably 1-1.1, more preferably 1-1.05; the carburizing heat treatment is preferably carried out in a carburizing atmosphere furnace; the temperature of the second salt bath isothermal quenching is preferably 200-250°C, more preferably 220-240°C, the isothermal holding time is preferably 20-30min, more preferably 22-25min, and after isothermal holding, it is preferably water cooled to room temperature. In the present invention, after heat treatment by such a heat treatment system, the surface C content of the ultra-high strength steel is 0.90-1.0 wt.%.

[0075] In the present invention, when the metallographic structure of the ultra-high strength steel includes tempered troostite, the heat treatment preferably includes: quenching and tempering the steel profile in sequence; the heating temperature of the quenching is preferably 870-890°C, more preferably 875-880°C, further preferably 880°C, and the holding time is preferably 20-30min, more preferably 22-25min; the heating process of the quenching is preferably carried out under argon protection; the cooling method of the quenching is preferably water cooling and air cooling in sequence; the temperature of the water for water cooling is preferably 40°C, and the time of the water cooling is preferably 5-10 seconds; the air cooling is preferably air cooling to room temperature; the temperature of the tempering is preferably 480-520°C, more preferably 500°C; the holding time of the tempering is preferably 40-60min, more preferably 45-55min; the cooling method of the tempering is preferably water cooling, specifically water cooling to room temperature; the tempering is preferably carried out under nitrogen protection. The present invention first transforms pearlite and a small amount of ferrite into austenite by heat treatment at 870-890°C, transforms austenite into martensite after cooling, and transforms martensite into tempered troostite after tempering. In the present invention, after heat treatment by the heat treatment system here, the metallographic structure of the obtained ultra-high strength steel is mainly tempered troostite, and also includes a small amount of ferrite.

[0076] The present invention also provides an ultra-high strength steel prepared by the preparation method described in the above scheme; the metallographic structure of the ultra-high strength steel includes nanosheet twinned martensite; or the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite, or the metallographic structure of the ultra-high strength steel includes tempered troostite.

[0077] In the present invention, when the metallographic structure of the ultra-high strength steel includes nanosheet twinned martensite, the volume fraction of nanosheet twinned martensite in the metallographic structure is preferably 98-100%; the tensile strength of the ultra-high strength steel is above 2.7 GPa, preferably 2.7-2.8 GPa, the elongation is above 9%, preferably 9-10%, and the yield strength is preferably above 1.8 GPa, more preferably 1.8-2.2 GPa.

[0078] In the present invention, when the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite, the volume fraction of medium carbon martensite in the metallographic structure of the core is preferably 85-90%, and the volume fraction of lower bainite is preferably 10-15%; the volume fraction of high carbon martensite in the surface metallographic structure is preferably 80-90%, the volume fraction of granular carbide is preferably 5-10%, and the volume fraction of lower bainite is preferably 5-10%; the surface hardness of the ultra-high strength steel is 62-64HRC, and the surface hardness is 850-950HV.

[0079] In the present invention, when the metallographic structure of the ultra-high strength steel includes tempered troostite, the volume fraction of tempered troostite in the metallographic structure is preferably 80-90%; the yield strength of the ultra-high strength steel is above 1300 MPa, preferably 1300-1500 MPa, the tensile strength is above 1500 MPa, preferably 1500-1700 MPa, and the elongation is above 10%, preferably 10-15%.

[0080] The present invention also provides the use of the ultra-high strength steel with a metallographic structure of nano-lamellar twin martensite in aircraft landing gear, bearings, bridge cables, bolts and molds as described in the above scheme.

[0081] The present invention also provides the use of ultra-high strength steel described in the above scheme, wherein the core metallographic structure is medium carbon martensite and lower bainite, and the surface metallographic structure is high carbon martensite, granular carbide and lower bainite in wear-resistant products; the wear-resistant products specifically include bearing rollers or tools and dies.

[0082] The present invention also provides the use of the tempered troostite ultra-high strength steel described in the above scheme in an elastic component; the elastic component preferably includes one or more of elastic bars, springs and elastic gaskets.

[0083] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0084] Example 1

[0085] according to Figure 1 The steel profiles are prepared according to the process in the following steps:

[0086] The scrap railway spring bars with the grade of 60Si2MnA, the scrap automobile leaf springs with the grade of 50CrVA and the scrap shafts with the grade of 40CrNiMo were shot blasted and cleaned, and then the three grades of scrap steel were mixed in a mass ratio of 5:2:1 and preheated for 30 minutes in a nitrogen protection environment at 600℃. The preheated scrap steel was put into the electric arc furnace for rough refining. During the rough refining process, argon was used for stirring. Silicon iron, manganese iron, aluminum-containing deoxidizer, molybdenum iron, vanadium iron, waste copper wires with insulation removed, and niobium iron were added in time to control the alloy composition in the molten steel. The tapping temperature of the electric arc furnace was controlled at 1750℃, and the bottom argon was opened 5 minutes before the tapping of the electric furnace. The large amount of stirring during the tapping process ensured that the alloy was fully melted. A clean turnover ladle was used to ensure the tapping of the red envelope, and the ladle baking temperature was 1200℃.

[0087] From ladle to refining, argon gas stirring is used, and the refining process ensures the refining submerged arc operation. The ladle refining temperature is controlled at 1700℃ and the refining time is 50min. After refining, the molten steel is transferred to the tundish, and then degassed and cast under vacuum conditions to obtain a steel ingot with a diameter of 300mm. During vacuum casting, the temperature of the molten steel is controlled at 1650℃, and the vacuum degree of the vacuum chamber is maintained at 30Pa.

[0088] The composition of the steel ingot obtained through the above steps is as follows: C: 0.54wt.%, Si: 1.6wt.%, Mn: 1.0wt.%, Mo: 0.15wt.%, V: 0.15wt.%, Cr: 0.30wt.%, Ni: 0.15wt.%, Cu: 0.05wt.%, Nb: 0.01wt.%, Al: 0.04wt.%, P: 0.010wt.%, S: 0.010wt.%, O: 12ppm, N: 15ppm, and the balance is Fe.

[0089] A steel ingot with a diameter of 300 mm is forged into a square billet of 160×160 mm. The initial forging temperature is controlled at 1100°C and the final forging temperature is controlled at 1000°C.

[0090] The forged steel billet is rolled using the residual heat from forging, and after multiple hot rolling passes, a steel wire with a diameter of 15 mm is formed. The initial rolling temperature is controlled at 950°C, and the final rolling temperature is controlled at 875°C. The steel wire obtained after rolling is placed in a furnace at 600°C for 10 minutes, then taken out and air-cooled to room temperature, and then the steel wire is surface processed to remove 1 mm of diameter and fully remove the surface oxide scale and decarburized layer.

[0091] Figure 2 The metallographic structure of the steel wire obtained in this example is shown in Figure 2, where the scale on the left is 250 μm and the scale on the right is 50 μm. Figure 2 It can be seen that the metallographic structure of the unheat-treated steel wire is a small amount of ferrite (white) + pearlite, and the structure is fine and evenly distributed.

[0092] Example 2

[0093] The steel wire rod after removing the surface oxide scale and decarburized layer in Example 1 was heated to 880°C under nitrogen protection, kept warm for 20 minutes, and then kept isothermally warm in a salt bath at 160°C for 25 minutes, and then taken out and water-cooled to room temperature to obtain ultra-high strength steel. After testing, the obtained ultra-high strength steel has a tensile strength of 2.765GPa, a yield strength of 1.950GPa, and an elongation of 9.0%. It has both ultra-high strength and good plasticity, and can be used in the preparation of ultra-high strength bridge cables.

[0094] Figure 3The metallographic structure morphology of the ultra-high strength steel obtained after heat treatment in this embodiment, wherein the scale on the left is 250 μm, and the scale on the right is 50 μm; Figure 4 This is a SEM image of the microstructure of the ultra-high strength steel obtained after heat treatment in this embodiment, where the scale on the left is 4 μm and the scale on the right is 2 μm. Figure 3-4 It can be seen that after austenitizing heat treatment and salt bath isothermal quenching, the metallographic structure morphology of the obtained ultra-high strength steel is mainly the martensite morphology obtained by isothermal quenching.

[0095] The distribution of the main alloying elements of the ultra-high strength steel obtained in this embodiment was obtained by surface scanning using the energy spectrometer in the SEM. The results are as follows: Figure 5 As shown, the scale bars are 10 μm. Figure 5 It can be seen that the main alloying elements such as C, Si, Mn, Mo, and V are evenly distributed inside the steel.

[0096] The microstructure of the ultra-high strength steel obtained in this embodiment was observed using a transmission electron microscope (TEM). Figure 6 shown. Figure 6 a and b are bright field phases, c is dark field phase, d is diffraction spot, the scale of a is 100nm, the scale of b and c is 20nm, and the scale of d is 21 / nm. Figure 6 It can be seen that the martensite lamellae of the ultra-high strength steel prepared in this embodiment have an ultra-fine nanostructure, and the diffraction spots indicate that the martensite has twin structure characteristics, and this organization has ultra-high strength and good plasticity.

[0097] The nano alloy carbide precipitation phase of the high strength steel obtained in this embodiment was observed using a transmission electron microscope (TEM), and the results obtained are as follows: Figure 7 shown. Figure 7 a is a bright field image, b is a dark field image, c is a high-resolution image of the interface with the matrix, d is a diffraction spot, e, f, g, h are the distribution of alloy elements in the precipitated phase, where the scales of a, b, e, f, g and h are all 50nm, the scale of c is 2nm, and the scale of d is 21 / nm. Figure 7 It can be seen that the precipitated phase is alloy carbide with nanometer scale.

[0098] Comparative Example 1

[0099] The steel wire rod after removing the surface oxide scale and decarburized layer in Example 1 was heated to 880°C under nitrogen protection, kept warm for 20 minutes, then oil-cooled to room temperature, then low-temperature tempered at 160°C for 25 minutes, and then water-cooled to room temperature to obtain a steel sample. After testing, the tensile strength of the obtained steel sample was 2.745 GPa, the elongation was 6.3%, and the yield strength was 1.920 GPa.

[0100] Figure 8 The metallographic structure morphology of the steel sample obtained after heat treatment in this comparative example, wherein the scale bar on the left is 250 μm, and the scale bar on the right is 50 μm; Fig. 9 This is a SEM image of the microstructure of the steel sample obtained after heat treatment in this comparative example, where the scale on the left is 4μm and the scale on the right is 2μm. Figure 8-Figure 9 It can be seen that after 880℃ oil quenching + 160℃ low-temperature tempering, the structure of the obtained steel sample is mainly tempered martensite.

[0101] Fig.10 The stress-strain curves of the unheat-treated wire, the ultra-high strength steel obtained in Example 2, and the steel sample obtained in Comparative Example 1, wherein 880°C+160°C isothermal quenching represents the ultra-high strength steel obtained in Example 2, and 880°C quenching+160°C tempering represents the steel sample obtained in Comparative Example 1. Fig.10 It can be seen that the ultra-high strength steel prepared in Example 2 has better plasticity while maintaining ultra-high strength, while the plasticity of the steel sample obtained in Comparative Example 1 is significantly lower than that in Example 2. The above results show that after the heat treatment of the present invention, a steel with both ultra-high strength and good plasticity can be obtained.

[0102] Example 3

[0103] The steel wire after removing the surface oxide scale and decarburized layer in Example 1 was placed in a carburizing atmosphere furnace and heated to 880°C, kept warm for 1 hour, and the carbon potential was controlled at 1.1. After the insulation was completed, the sample was taken out and placed in a 250°C salt bath for isothermal insulation for 30 minutes, then taken out and water-cooled to room temperature to obtain ultra-high strength steel. After testing, the surface hardness of the obtained ultra-high strength steel was 62-64HRC, and the surface hardness was 920HV. The ultra-high strength steel obtained in this example has excellent wear resistance and can be used in the preparation of products such as bearing rollers and tools.

[0104] Fig.11 The surface metallographic structure morphology (left, scale is 100 μm) and hardness distribution curve (right) of the ultra-high strength steel obtained after heat treatment in this embodiment. Fig.11 It can be seen that the surface layer structure of the ultra-high strength steel obtained in this embodiment is granular carbide + high carbon martensite + lower bainite structure, and the core structure is medium carbon martensite + lower bainite structure; the hardness distribution curve shows that the surface of the obtained ultra-high strength steel has a higher hardness.

[0105] Example 4

[0106] The steel wire after removing the surface oxide scale and decarburized layer in Example 1 was heated to 880°C under argon protection, kept warm for 20 minutes, then cooled in 40°C water for 10 seconds, taken out and air-cooled to room temperature, then tempered under 500°C nitrogen protection for 50 minutes, taken out and water-cooled to room temperature, to obtain ultra-high strength steel. After testing, the yield strength of the obtained ultra-high strength steel was 1386MPa, the tensile strength was 1575MPa, and the elongation was 14%, which can be used for the preparation of products such as spring bars, springs, and elastic gaskets.

[0107] Fig.12 The metallographic structure morphology (left, scale is 50 μm) and stress-strain curve (right) of the ultra-high strength steel obtained after heat treatment in this embodiment. Fig.12 It can be seen from the metallographic structure morphology in that the main structure of the ultra-high strength steel prepared in this embodiment is tempered troostite, and also includes a small amount of ferrite (white); Fig.12 It can be seen from the stress-strain curve in that the ultra-high strength steel obtained in this embodiment has good plasticity.

[0108] Example 5

[0109] The scrap railway spring bars with the grade of 60Si2MnA, the scrap automobile leaf springs with the grade of 50CrVA and the scrap shafts with the grade of 40CrNiMo were shot blasted and cleaned, and then the three grades of scrap steel were mixed in a mass ratio of 6:3:1 and preheated for 40 minutes in a nitrogen protection environment at 500℃. The preheated scrap steel was put into the electric arc furnace for rough refining. During the rough refining process, argon was used for stirring. Silicon iron, manganese iron, aluminum-containing deoxidizer, molybdenum iron, vanadium iron, waste copper wires with insulation removed, and niobium iron were added in time to control the alloy composition in the molten steel. The tapping temperature of the electric arc furnace was controlled at 1700℃, and the bottom argon was opened 5 minutes before the tapping of the electric furnace. The large amount of stirring during the tapping process ensured that the alloy was fully melted. A clean turnover ladle was used to ensure the tapping of the red envelope, and the ladle baking temperature was 1100℃.

[0110] From ladle to refining, argon gas stirring is used, and the refining process ensures the refining submerged arc operation. The ladle refining temperature is controlled at 1700℃ and the refining time is 60min. After refining, the molten steel is transferred to the tundish, and then degassed and cast under vacuum conditions to cast into a steel ingot with a diameter of 300mm. During vacuum casting, the temperature of the molten steel is controlled at 1650℃, and the vacuum degree of the vacuum chamber is maintained at 40Pa.

[0111] The composition of the steel ingot obtained through the above steps is as follows: C: 0.57wt.%, Si: 1.7wt.%, Mn: 0.88wt.%, Mo: 0.17wt.%, V: 0.14wt.%, Cr: 0.35wt.%, Ni: 0.15wt.%, Cu: 0.06wt.%, Nb: 0.02wt.%, Al: 0.03wt.%, P: 0.009wt.%, S: 0.009wt.%, O: 10ppm, N: 18ppm, and the balance is Fe.

[0112] The steel ingot with a diameter of 300 mm is forged into a square steel billet of 160×160 mm. The initial forging temperature is controlled at 1050°C and the final forging temperature is controlled at 950°C.

[0113] The forged steel billet is rolled using the residual heat from forging, and after multiple hot rollings, a steel wire with a diameter of 20 mm is formed. The initial rolling temperature is controlled at 900°C, and the final rolling temperature is controlled at 850°C. The steel wire obtained after rolling is placed in a furnace at 600°C for 10 minutes, then taken out and air-cooled to room temperature, and then the steel wire is surface processed to remove 1 mm of diameter and fully remove the surface oxide scale and decarburized layer.

[0114] Example 6

[0115] The steel wire rod after removing the surface oxide scale and decarburized layer in Example 5 was heated to 870°C under nitrogen protection, kept warm for 30 minutes, and then kept isothermally in a salt bath at 170°C for 40 minutes, and then taken out and water-cooled to room temperature to obtain ultra-high strength steel. After testing, the obtained ultra-high strength steel had a tensile strength of 2.71 GPa, a yield strength of 1.84 GPa, and an elongation of 9.6%.

[0116] Example 7

[0117] The steel wire rod after removing the surface oxide scale and decarburized layer in Example 5 was placed in a carburizing atmosphere furnace and heated to 890°C for 1 hour, and the carbon potential was controlled at 1.0. After the insulation, the sample was taken out and placed in a 200°C salt bath for 25 minutes, and then taken out and water-cooled to room temperature to obtain ultra-high strength steel. After testing, the surface hardness of the obtained ultra-high strength steel was 64HRC and the surface hardness was 930HV.

[0118] Example 8

[0119] The steel wire rod after removing the surface oxide scale and decarburized layer in Example 5 was heated to 890°C under argon protection, kept warm for 30 minutes, then cooled in 40°C water for 5 seconds, taken out and air-cooled to room temperature, then tempered at 480°C under nitrogen protection for 60 minutes, taken out and water-cooled to room temperature, and ultra-high strength steel was obtained. After testing, the yield strength of the obtained ultra-high strength steel was 1390MPa, the tensile strength was 1589MPa, and the elongation was 11%.

[0120] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing ultra-high strength steel, characterized in that: The following steps are involved: The alloy raw materials are melted and then cast to obtain a steel ingot; The chemical composition of the steel ingot includes: C: 0.53-0.57wt.%, Si: 1.5-1.8wt.%, Mn: 0.80-1.0wt.%, Mo: 0.15-0.20wt.%, V: 0.10-0.15wt.%, Cr: 0.30-0.40wt.%, Ni: 0.10-0.15wt.%, Cu: 0.05-0.08wt.%, Nb: 0.01-0.02wt.%, Al≤0.05wt.%, P≤0.010wt.%, S≤0.010wt.%, O≤12ppm, N≤20ppm, and the balance is Fe; Forging and rolling the steel ingot in sequence to obtain a steel profile; The steel profile is heat treated to obtain the ultra-high strength steel; the metallographic structure of the ultra-high strength steel includes nano-sheet twinned martensite; or the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite; or the metallographic structure of the ultra-high strength steel includes tempered troostite.

2. The preparation method according to claim 1, characterized in that: The alloy raw materials include scrap steel with a grade of 60Si2MnA, scrap steel with a grade of 50CrVA and scrap steel with a grade of 40CrNiMo.

3. The preparation method according to claim 2, characterized in that: The scrap steel with the grade of 60Si2MnA is scrap railway spring bars; the scrap steel with the grade of 50CrVA is scrap automobile leaf springs; and the scrap steel with the grade of 40CrNiMo is scrap shafts.

4. The preparation method according to claim 2, characterized in that: The smelting comprises: coarsely refining the alloy raw material and then adjusting and refining the alloy elements in sequence.

5. The preparation method according to any one of claims 2 to 4, characterized in that: The mass ratio of the scrap steel with the grade of 60Si2MnA, the scrap steel with the grade of 50CrVA and the scrap steel with the grade of 40CrNiMo is (4-6):(2-4):(1-2).

6. The preparation method according to claim 4, characterized in that: Before the rough refining, the alloy raw materials are subjected to surface cleaning and preheating treatment in sequence.

7. The preparation method according to claim 6, characterized in that: The surface cleaning is shot blasting cleaning.

8. The preparation method according to claim 6, characterized in that: The temperature of the preheating treatment is 500-600° C., and the time is 30-50 min. The preheating treatment is carried out under nitrogen protection.

9. The preparation method according to claim 4, characterized in that: The raw materials used for adjusting the alloy elements include one or more of ferrosilicon, ferromanganese, aluminum-containing deoxidizer, ferromolybdenum, ferrovanadium, waste copper wire with insulation removed, and ferroniobium.

10. The preparation method according to claim 4, characterized in that: The rough refining is electric arc furnace rough refining; and the refining is ladle refining.

11. The preparation method according to claim 4 or 9, characterized in that: After the alloy elements are adjusted, the steel is tapped from an electric arc furnace at a temperature of 1700-1750° C., and argon is blown from the bottom 5-10 minutes before the steel is tapped.

12. The preparation method according to claim 4 or 10, characterized in that: The refining temperature is 1680-1720° C., the refining time is 40-60 min, and argon is blown and stirred throughout the refining process.

13. The preparation method according to claim 1, characterized in that: The casting is vacuum casting; the temperature of the molten steel during the vacuum casting is 1630-1670° C.; the vacuum degree of the vacuum casting is 30-50 Pa.

14. The preparation method according to claim 13, characterized in that: Before the vacuum casting, the molten steel is also vacuum degassed.

15. The preparation method according to claim 1, characterized in that: The initial forging temperature of the forging is 1050-1100°C, and the final forging temperature is 950-1000°C.

16. The preparation method according to claim 1, characterized in that: The rolling is hot rolling; the initial rolling temperature of the hot rolling is 900-950° C., and the final rolling temperature is 850-875° C.; the number of hot rolling passes is 8-10 passes; and the deformation rate of the hot rolling passes is 5%-15%.

17. The preparation method according to claim 1, characterized in that: The steel profile is a steel wire; the diameter of the steel wire is 15 to 30 mm.

18. The preparation method according to claim 1, characterized in that: When the metallographic structure of the ultra-high strength steel includes nanosheet twin martensite, the heat treatment includes: subjecting the steel profile to austenitizing heat treatment and salt bath isothermal quenching in sequence; the temperature of the austenitizing heat treatment is 870-890°C, and the holding time is 20-30 minutes; the austenitizing heat treatment is carried out under nitrogen protection; the temperature of the salt bath isothermal quenching is 150-180°C, the isothermal holding time is 20-40 minutes, and water cooling to room temperature after isothermal holding.

19. The preparation method according to claim 1, characterized in that: When the core metallographic structure of the ultra-high strength steel includes medium-carbon martensite and lower bainite, and the surface metallographic structure includes high-carbon martensite, granular carbide and lower bainite, the heat treatment includes: subjecting the steel profile to carburizing heat treatment and salt bath isothermal quenching in sequence; the carburizing heat treatment temperature is 870-890°C, the holding time is 1-2h, and the carbon potential is 1-1.1; the salt bath isothermal quenching temperature is 200-250°C, the isothermal holding time is 20-30min, and water cooling to room temperature after isothermal holding.

20. The preparation method according to claim 19, characterized in that: When the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite, the surface C element content of the ultra-high strength steel is 0.90-1.0wt.%.

21. The preparation method according to claim 1, characterized in that: When the metallographic structure of the ultra-high strength steel includes tempered troostite, the heat treatment includes: quenching and tempering the steel profile in sequence; the heating temperature of the quenching is 870-890°C, the holding time is 20-30 minutes, and the heating process of the quenching is carried out under argon protection; the cooling method of the quenching is water cooling and air cooling in sequence; the temperature of the water for water cooling is 40°C, and the water cooling time is 5-10 seconds; the air cooling is air cooling to room temperature; the tempering temperature is 480-520°C, and the holding time is 40-60 minutes; the tempering is carried out under nitrogen protection; the cooling method of the tempering is water cooling.

22. An ultra-high strength steel prepared by the preparation method according to any one of claims 1 to 21; the metallographic structure of the ultra-high strength steel includes nano-lamellar twinned martensite; or the core metallographic structure of the ultra-high strength steel includes medium carbon martensite and lower bainite, and the surface metallographic structure includes high carbon martensite, granular carbide and lower bainite; or the metallographic structure of the ultra-high strength steel includes tempered troostite.

23. The ultra-high strength steel according to claim 22, characterized in that: When the metallographic structure of the ultra-high strength steel includes nanosheet twin martensite, the volume fraction of the nanosheet twin martensite in the metallographic structure is 98-100%; the tensile strength of the ultra-high strength steel is above 2.7 GPa, the yield strength is above 1.8 GPa, and the elongation is above 9%.

24. The ultra-high strength steel according to claim 22, characterized in that: When the core metallographic structure of the ultra-high strength steel includes medium-carbon martensite and lower bainite, and the surface metallographic structure includes high-carbon martensite, granular carbide and lower bainite, the volume fraction of medium-carbon martensite in the core metallographic structure is 85-90%, and the volume fraction of lower bainite is 10-15%; the volume fraction of high-carbon martensite in the surface metallographic structure is 80-90%, the volume fraction of granular carbide is 5-10%, and the volume fraction of lower bainite is 5-10%; the surface hardness of the ultra-high strength steel is 62-64HRC, and the surface hardness is 850-950HV.

25. The ultra-high strength steel according to claim 22, characterized in that: When the metallographic structure of the ultra-high strength steel includes tempered troostite, the volume fraction of tempered troostite in the metallographic structure is 80-90%; the yield strength of the ultra-high strength steel is above 1300 MPa, the tensile strength is above 1500 MPa, and the elongation is above 10%.

26. Use of the ultra-high strength steel according to claim 23 in aircraft landing gears, bearings, bridge cables, bolts and moulds.

27. Use of the ultra-high strength steel according to claim 24 in wear-resistant products.

28. Use of the ultra-high strength steel according to claim 25 in elastic components.

Citation Information

Patent Citations

  • Maraging steel

    CN103484787A

  • A precipitation haredning steel and its manufacture

    CN109642299A